Changes in the Length of the Neuraminidase Stalk Region Impact H7N9 Virulence in Mice - Bi, Yuhai; Xiao, Haixia; Chen, Quanjiao; Wu, Yan; Fu, Lifeng; Quan, Chuansong; Wong, Gary; Liu, Jun; Haywood, Joel; Liu, Yingxia; Zhou, Boping; Yan, Jinghua; et al. (Journal of virology, 2016)
The neuraminidase stalk of the newly emerged H7N9 influenza virus possesses a 5-amino-acid deletion. This study focuses on characterizing the biological functions of H7N9 with varied neuraminidase stalk lengths. Results indicate that the 5-amino-acid deletion had no impact on virus infectivity or replication in vitro or in vivo compared to that of a virus with a full-length stalk, but enhanced virulence in mice was observed for H7N9 encoding a 19- to 20-amino-acid deletion, suggesting that N9 stalk length impacts virulence in mammals, as N1 stalk length does.